Impact of Boko Haram Insurgency on Governance and Socio-Economic Development in Borno State, Nigeria - Emmanuel, Joseph; Yusufari, Adamu Gujungu; Chuga, Jennifer Finyien (Darul Yasin Al Sys, 2025)
This study examined the impact of Boko Haram insurgency on governance and socio-economic development in Borno State, Nigeria. Using a descriptive survey design, the study targeted 553 respondents comprising district heads, ward councillors, local government chairmen, and members of the State House of Assembly. A purposive sampling technique was employed to select 139 participants, and data was collected using a structured questionnaire and key informant interviews. Findings revealed that the insurgency significantly weakened state institutions, disrupted electoral processes, eroded public trust in governance, and fostered corruption and lawlessness. On the socio-economic front, the insurgency caused widespread destruction of infrastructure, disrupted trade and investment, hindered access to education and healthcare, displaced populations, and escalated poverty. The study concluded that the Boko Haram insurgency poses serious challenges to governance and socio-economic development in Borno State. Recommendations were made for strengthening state institutions, enhancing security operations, promoting economic recovery, supporting displaced persons, and initiating long-term peacebuilding programs to address the root causes of the conflict and foster sustainable development.